Religious and Inter-Religious Tolerance in an Islamic Perspective - Herdiana; Yosep Maulana; Gagan Ganeswara; Ujang Permana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses Religious Tolerance. In an Islamic perspective, tolerance is simply a person's effort to restrain themselves or be patient with things that are not in line with themselves (Sabir, 2016). By implementing tolerance, it is hoped that conflicts between individuals or groups will never occur. This article aims to discuss Religious Tolerance from an Islamic Perspective. Research Method: library study approach, literature study is a theoretical study, references and scientific literature related to the norms of the social situation being observed. Literature sources are then analyzed and concluded. The main principle of tolerance according to Islam, As a theological advocate of tolerance, Islam will never hinder tolerance in the name of religion. However, as a religion that strictly maintains the purity of the Aqidah of Tauhidiah and Sharia, Islam strictly prohibits tolerant behavior that leads to syncretism. Tolerance must be implemented, but the purity of the creed of monotheism and Islamic sharia must be maintained.